Participación de los factores de crecimiento FCF1, NRG y sus receptores en la regulación de la proliferación celular durante la morfogénesis de los tercios medio y apical del tabique interventricular en embrión de pollo - Contreras Ramos, Alejandra (Universidad Autónoma Metropolitana, 2008)
The interventricular septum (IVS) is constituted by three regions. The basal third (mesenchymal component) originates from the endocardial cushions of the atrioventricular canal and the conal ridges. The medial and apical thirds (muscular component) originate by the fusion of the ventricular trabeculations. It is now also known that the developing IVS as well as the ventricular cavities grow in opposite direction to the atria. That embryonic and anatomic complexity determinates that the absence or anomalous development of trabeculations and IVS results into very complex congenital cardiac defects as hypoplastic right or left ventricle and univentricular heart. On the other hand, using modern molecular and genetic techniques, it has been discovered that during embryonic development and post natal life, fibroblast growth factors (FGFs) and the endocardial derived neuregulin 1 (NRG1) are two major signal transduction pathways which play a variety of roles in the development and function of myocytes. Survival and antiapoptotic activities, cell proliferation, cell to cell interaction, cell differentiation and myocardial lineage specification are some functions mediated by FGFs and NRG1. Although this knowledge, integration of morphogenetic process involved in the development of the muscular region of the IVS and molecular regulation is scarcely known. To gain insight into this subject we correlated the temporal and spatial pattern of cyclic and apoptotic myocytes and the distribution of FGF1, NRG1, RFGR, ErbB2 and ErbB4, in the ventricular region of the heart of chicken embryos during cardiac septation (Hamburger and Hamilton stages ranging through 18-30HH). For this purpose, Western Blotting (WB), Flow Cytometry (FC), Immunohistochemistry (IHQ) and RT-PCR were performed. The temporal and spatial pattern of expression of NRG1mRNA was also determined in histological sections by in situ hybridization (ISH). Trabeculations, IVS, and ventricular free wall were discriminated in IHQ and ISH analysis. It was confirmed that trabeculations of the right and left ventricular walls gradually appose, adhere, and fuse to a central trabeculation which corresponds to that projected above the interventricular groove to form the developing IVS. Likewise, evidences were shown that the differential increase at the muscular ventricular mass depends on myocytic proliferation. The temporal and spatial pattern of high-intensity foci of cyclic myocytes determines that trabeculations, developing IVS and ventricular chambers expand in opposite direction to the atria. It was found by FC that the main cyclic activity (S, G2/M phases) on cell at the ventricular region corresponded to st. 18-26HH. At st. 28-30HH more than 73% of cells were determined to be in the G1-G0 phase. The most persistent high I-M, I-BrdU and IPCNA were always found at the epicardial surface of the ventricular wall, at the inferior region of the central trabeculation (stages 18-22HH) and at the inferior border of the developing septum (stage 24HH onward). TUNEL, LysoTracker labelling and immunolocalization of apoptotic proteins did not showed any evidence that this process could be important in the development of the muscular zone of the IVS. All these results together with those by in vivo labelling which demonstrate that the prospective place of the IVS appears at the straight tube heart stage, indicate that morphogenesis of the muscular region of the IVS occurs in three phases: 1. Premorphogenetic, 2. Morphogenetic and 3. Histodifferentiation. Correlation of the temporal and spatial pattern of expression of FGF1, NRG1, FGFR, ErbB2 and ErbB4 with distribution of cyclic and apoptotic myocytes was determined based on this classification. The results indicate that although FGF1 is not involved in proliferation of the embryonic ventricular myocytes, it is possible that FCFR1 together with any different FGF could be implicated. NRG1 mRNA was found expressed in the endocardium and myocardium while ErbB2/4 mRNAs were expressed only in the myocardium. Based in these facts, we suppose that NRG1 could be regulating two different processes. At the beginning of the IVS development (st 17- 20HH) the endocardial derived NRG1 signalling pathway via ErbB 2/4 receptors is essential for trabeculation of the ventricular myocardium. Later from stage 28HH onward the myocardial derived NRG1 signalling pathway via ErbB 4/4 determines myocardial maturation.; El tabique interventricular (TI-V) consta de tres tercios. El basal (componente fibroso) derivado de los cojines del canal atrioventricular y crestas del cono. Los tercios medio y apical (componente muscular) se originan por la fusión progresiva de las trabéculas ventriculares y al igual que las cavidades ventriculares durante su desarrollo crece en sentido apuesto a los atrios. Esta complejidad anatómica y embriológica determina que la ausencia o desarrollo anómalo de trabéculas o TI-V produzca cardiopatías congénitas complejas como hipoplasias ventriculares y corazón univentricular. Por otro lado, por técnicas modernas de biología molecular y genética se ha descubierto que durante el desarrollo embrionario y en la vida postnatal los factores de crecimiento fibroblasticos (FCFs) y la neuregulina1 (NRG1) representan dos vías de señalización que regulan diversas actividades de los miocitos. Entre las funciones que se les atribuyen están supervivencia, protección contra apoptosis, proliferación, interacción célula-célula, diferenciación y especificación del linaje miocárdico. No obstante, es necesario integrar los procesos morfogenéticos responsables del desarrollo de la región muscular del TI-V con la regulación molecular de este proceso. Para obtener esta información, se correlacionaron los patrones espacio-temporales de miocitos ventriculares cíclicos y apoptoticos con la distribución de FCF1, NRG1 y sus receptores respectivos (RFCF, ErbB2 y ErbB4) en el corazón de embriones de pollo durante el proceso de septación cardiaca (estadios de Hamburger y Hamilton 18-30). Se hicieron análisis por Western Blot (WB), Citometría de Flujo (CF), Inmunohistoquímica (IHQ), RT-PCR e hibridación in situ (HIS). El análisis de los resultados de IHQ e HIS se determinaron distinguiendo paredes, trabéculas y TI-V en desarrollo. Se confirmó la prevalecencia de la trabécula central, a la que conforme avanza el desarrollo se ancla el resto de las trabéculas para originar la porción muscular del TI-V. Así mismo se mostraron evidencias de que la proliferación de los miocitos es el mecanismo regulador del incremento diferencial de la masa muscular ventricular. La distribución espacio-temporal de este proceso determina el sentido de crecimiento de trabéculas, TIV en desarrollo y cámaras ventriculares en sentido opuesto a los atrios. Por CF se determinó que la mayor actividad cíclica (fases S o G2/M) de las células de la región ventricular se presentó entre sts 18-26HH. Durante los sts 28-30HH más del 73% de las células fue determinada en fase G1-G0. Los valores mayores de I-M, I-BrdU, I-PCNA siempre se hallaron en la superficie epicardica de las paredes ventriculares, región inferior de la trabécula central (st. 18-22HH) y borde inferior del TI-V en desarrollo (del st. 24HH en adelante). Los resultados de TUNEL, marcaje con LysoTracker e inmunolocalización de proteínas apoptóticas, no apoyan la participación de este proceso en el desarrollo de la región muscular del TI-V. Estos hallazgos junto con los resultados de marcaje in vivo que señalan que el sitio prospectivo del TI-V aparece en la etapa de corazón en tubo recto, indican que el desarrollo del tabique sucede en tres fases: 1. Premorfogenética, 2. Morfogenética y 3. Crecimiento e/o histodiferenciación. Dicha clasificación fue empleada para correlacionar la expresión espacio-temporal de las proteínas (FCF1, NRG1 FGFR, ErbB2 y ErbB4) con la actividad cíclica y apoptótica de los miocitos ventriculares. Los resultados de FCF1 indican que esta proteína no esta relacionada con los procesos de proliferación de los miocitos ventriculares, sin embargo la expresión temporal del RFCF sugiere su participación en la regulación de la actividad mitótica de miocitos ventriculares acoplado a un FCF distinto al 1. El RNAm de NRG se expresó en endocardio y miocardio; en contraste RNAm de ErbB2/ y ErbB4 se expresaron exclusivamente en el miocardio. Basados en estos hechos, suponemos que durante el desarrollo del TI-V existen dos procesos regulados por NRG1. Primero (sts 17-20HH) mediante regulación parácrina el complejo NRG1/ErbB2/4 controla la morfogénesis de las láminas trabeculares. Más tarde (st. 28HH en adelante) por regulación autócrina NRG1/ErbB4/4 determina la maduración miocárdica.